Realisasi Pajak Reklame, Potensi Pajak Reklame Dan Efektivitas Pajak Reklame Terhadap Pendapatan Asli Daerah Kabupaten Boyolali - Bella Dwi Saputri; Hadi Samanto; Sri Laksmi Pradanawati (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This study aims to analyze the influence of billboard tax realization, potential, and effectiveness on the Regional Original Revenue (PAD) of Boyolali Regency during the 2020–2024 period. The research adopts a quantitative approach using secondary data, with a total of 20 observations. The dependent variable in this study is PAD, while the independent variables include billboard tax realization, potential, and effectiveness. Data analysis was conducted using multiple linear regression. The findings indicate that the realization of billboard tax has a significant impact on PAD, while the effectiveness of billboard tax collection does not show a significant effect. This is evidenced by the t-test significance values, where the realization and potential variables have a significance level of 0.000 (< 0.05), while the effectiveness variable has a significance level of 0.408 (> 0.05). These results suggest that higher levels of tax realization and potential contribute positively to PAD. However, the effectiveness of tax collection alone does not necessarily lead to an increase in PAD, indicating a need for local government evaluation in optimizing tax collection efforts. Keywords: Billboard Tax Realization, Billboard Tax Potential, Billboard Tax Effectiveness, Regional Original Revenue (PAD). Keywords: Billboard Tax Realization, Billboard Tax Potential, Billboard Tax Effectiveness, Regional Original Revenue (PAD)